Floristic composition of a natural grassland in region of alto Camaquã, Rio Grande do Sul, Brazil (Semiárida, 2020)
Knowledge of floristic composition, diversity and modification of species that comprise a biome, contributes to the understanding of the ecological relationships of this. This is useful in the identifica tion of appropri ate management for a sustainable and ec onomic performance of pasture. In December 2011, we conducted a botanical survey, by the BOTANAL method in the city of Pinheiro Macha do in the region of Alto Cam aquã, part of Pampa biome in Brazil. In the survey 69 species were recorded, predominating speciesof grasses, Compositae and legumes families, being 33, 08 and 06 species respectively for each family, with predominance in the forage mass composition of Baccharis trimera, representing the Compositae, Paspalum notatum, representing grasses and Desmodium incanum, representing the legumes. The species Baccharis trimera and Eryngium horridum contributed with 49.78% of herbage mass. The remainder of the mass were consisted of 67 different species.
Keywords: Botanal; botanical composition; forage mass